Seasonal trends in emission of odorous gases from growing-finishing swine houses - KUMARI, PRIYANKA; CHOI, HONG-LIM (The Indian Journal of Animal Sciences, 2020)
The air quality in swine houses has caught attention of scientists and general public. The swine waste generates various odorous gases, which affects the health of farm workers and local residents. In this study, we investigated the composition and concentrations of three major groups (i.e. acidic, sulfuric and phenolic) of odorous gases in growing and fattening swine houses during winter and summer, and studied their relationship with aerial parameters (i.e. temperature and relative humidity). Among 10 different odorous gases measured, acetic acid was the most abundant odorous gas across both seasons. Except iso-valeric acid, dimethyl sulfide and dimethyl disulfide, the concentrations of other odorous gases varied significantly between winter and summer. The concentrations of these odorous gases were significantly higher in winter, except for p-cresol, which was significantly higher in summer. The aerial temperature showed significant positive correlations with concentrations of most of the acidic and sulfuric groups odorous gases, whereas, relative humidity was negatively correlated with concentrations of relatively fewer members of acidic and sulfuric groups odorous gases. The relationships studied here could be useful in regulating the emission of odorous gases from growing and fattening swine houses.